Ultrasociety. How 10,000 Years of War Made Humans the Greatest Cooperators on Earth (Terr@ Plural, 2020)
Para el biólogo Peter Turchin, guerras fuerán más importantes que la agricultura en el desarroyo y cooperación entre humanosTURCHIN, Peter (2016). Ultrasociety. How 10,000 years of war made humans the greatest cooperators on Earth. Chaplin: Beresta Books. 266 p. ISBN 10: 0996139516 - ISBN 13: 9780996139519